One-Year Patency of Valvulotomized Vein Grafts Is Similar to That of Arterial Grafts - Monsefi, Nadejda; Zierer, Andreas; Honarpisheh, Gazal; Bauer, Ralf; Kerl, Matthias; Beiras-Fernandez, Andres; Moritz, Anton (The Thoracic and Cardiovascular Surgeon, 2016)
Background Inferior vein graft patency after coronary artery bypass grafting (CABG) is attributed to various factors. Venous valves may limit flow, cause thrombus formation, and diminish diastolic backflow. The aim of our study was to compare clinical outcome and midterm patency rate of valvulotomized vein grafts and arterial grafts in patients undergoing CABG.Methods Between 2007 and 2010, valvulotomized saphenous vein segments were used to graft the right coronary artery (RCA) in 147 patients undergoing CABG with mean 2.8 ± 1 arterial and 1.5 ± 0.6 venous anastomoses. Outcome, reintervention, and reoperation were assessed after 4 ± 1.6 years. Intraoperative bypass flow rate was measured before and after valvulotomy of venous bypass grafts in 12 patients. Patency of the grafts was assessed by means of multislice computed tomography (MSCT) in 45 patients.Results A total of 102 patients underwent isolated CABG and 45 had combined procedures. In-hospital mortality was 2%. At 4 years' clinical follow-up, 95% of the patients were asymptomatic. Five patients underwent recoronary angiography because of angina pectoris. The MSCT and reangiography patency rate of all valvulotomized saphenous vein grafts was 97.1 versus 95.8% of arterial grafts 18 ± 6 months postoperatively. Intraoperative measurements showed a significant increase (+20.2 mL/min; p = 0.01) of flow in the venous bypass grafts to the RCA after valvulotomy. There were no reoperations at the latest follow-up.Conclusion Patients with valvulotomized venous grafts had good clinical outcome. The one-year patency rate of those grafts is comparable to that of arterial grafts. However, long-term results and angiography studies will be needed to strengthen these findings.
Keywords: coronary artery bypass grafting; computed tomography; outcomes